OTUD6B-AS1 Inhibits Viability, Migration, and Invasion of Thyroid Carcinoma by Targeting miR-183-5p and miR-21 - Wang, Zhuolu; Xia, Fada; Feng, Tiecheng; Jiang, Bo; Wang, Wenlong; Li, Xinying (Frontiers in Endocrinology, 2020)
Background The long noncoding RNA (lncRNA) functions as a regulator of initiation, progression, and metastasis of thyroid carcinomas. lncRNA OTUD6B antisense RNA 1 (OTUD6B-AS1) is a tumor-suppressive noncoding RNA in clear cell renal cell carcinoma. The role of OTUD6B-AS1 in thyroid carcinomas has not been reported yet. We aim to investigate the expression and biological functions of OTUD6B-AS1 in thyroid carcinomas. Methods The expression level of OTUD6B-AS1 was measured in 60 paired human thyroid carcinoma tissues and corresponding adjacent normal thyroid tissues. The correlations between the OTUD6B-AS1 expression levels and clinicopathological features were evaluated using the Mann-Whitney test. The effects of OTUD6B-AS1 on thyroid carcinoma cells were determined via the MTT and transwell assays. The potential targets of OTUD6B-AS1 were screened using the online programs OncomiR and StarBase 3.0, and the LncBase Predicted v.2. Luciferase reporter assay was used to confirm the interactions between OTUD6B-AS1 and its potential targets. Results OTUD6B-AS1 was downregulated in thyroid carcinoma tissue samples. The expression of OTUD6B-AS1 correlated with tumor size, clinical stage, and lymphatic metastasis of thyroid carcinoma. Overexpression of OTUD6B-AS1 significantly decreased the viability, migration, and invasion of thyroid carcinoma cells. Online programs predicted miR-183-5p and miR-21 as potential targets of OTUD6B-AS1. Luciferase reporter assays showed miR-183-5p and miR-21 bound to OTUD6B-AS1. Moreover, overexpression of miR-183-5p and miR-21 compromised the inhibitory effects of OTUD6B-AS1 on viability, migration, and invasion of thyroid carcinoma cells. Conclusions Taken together, our findings present in vitro evidence of lncRNA OTUD6B-AS1 as a tumor suppressor in thyroid carcinomas. OTUD6B-AS1 inhibits viability, migration, and invasion of thyroid carcinoma by targeting miR-183-5p and miR-21.